Prieto, Andrés I.: The Theologian and the Empire: A Biography of José de Acosta (1540–1600). Leiden, The Netherlands: Brill, 2024. 412 pp. - Lopes de Carvalho, Francismar Alex (Revista Complutense de Historia de América, 2025)
Review of: Prieto, Andrés I.: The Theologian and the Empire: A Biography of José de Acosta (1540–1600). Leiden, The Netherlands: Brill, 2024. 412 pp.